Alfabetização e letramento na escola multisseriada A´Uwê Uptabi Xavante - Tsu'utumrêmédi, Guinter Tsitsuru (Universidade Federal de São Carlos, 2023)
The objective of my research is to present the reality of the multigrade Indigenous school A´uwê Uptabi São José Tsira´mi, and to give visibility to the current challenge of the Xavante Indigenous teachers to teach literacy in the writing of both languages ​​- Xavante language and Portuguese language The idea of ​​my The project is to record how the process of building children's literacy takes place in the school space and in the Xavante culture. For this, I sought the knowledge of indigenous teachers and this rescue took place at the multi-grade indigenous school A´UWÊ UPTABI XAVANTE. The teachers and Paulo Freire entered into a dialogue for me to carry out this work. The child comes into contact with the world at the Xavante school, reading the world around, the day-to-day movement, in literacy and literacy of the Portuguese language in the pages of the book and in the world of wisdom. The construction of this TCC is the recovery of the value of the wisdom of indigenous teachers as the main protagonist, that is, it results from a construction process in writing in Portuguese and Xavante languages. Our intention with TCC is to transform traditional knowledge into meaningful learning.
Literacy and literacies in the multigrade school A´Uwê Uptabi Xavante
Keywords: Criança Xavante; Alfabetização; Escrita; Língua Portuguesa; Língua Xavante; Escola multisseriada; Xavante child; Literacy; Writing; Portuguese language; Xavante language; Multigrade School; Indigenous Teacher; CIENCIAS HUMANAS::EDUCACAO